Inhibition of human and simian immunodeficiency virus protease function by targeting Vpx-protease-mutant fusion protein into viral particles. - Wu, X (1996)
The human immunodeficiency virus type I (HIV-1) Vpr and HIV-2 Vpx proteins package into virions through interactions with their cognate Gag polyprotein precursor. The targeting properties of Vpr and Vpx have been exploited to incorporate foreign proteins into virions by expression as heterologous fusion molecules (X. Wu, H.-M. Liu, H. Xiao, J. Kim, P. Seshaiah, G. Natsoulis, J. D. Boeke, B. H. Hahn, and J. C. Kappes, J. Virol. 69:3389-3398, 1995). To explore the possibility of utilizing Vpx and Vpr to target dominant negative mutants of the HIV Pol proteins into virions, we fused HIV-2 Vpx with an enzymatically defective protease (PR) mutant. Using a vector system to facilitate transient coexpression with HIV provirus, Vpx-PR-mutant (VpxPR(M)) fusion protein was expressed and packaged efficiently into HIV-2 and simian immunodeficiency virus virions. Immunoblot analysis of purified virions demonstrated that the packaging of VpxPR(M) interfered with the processing of the Gag and Gag/Pol precursor proteins, similar to that of a well-characterized active-site PR inhibitor. The incomplete processing of Gag and Gag/Pol was consistent with a 25-fold reduction in virion infectivity. The coexpression of a packaging defective VpxPR(M) fusion protein with HIV-2 provirus produced virions with fully processed Gag protein, similar to wild-type virions. Importantly, virions trans complemented with a Vpx-chloramphenicol acetyltransferase fusion protein were normal with respect to the processing of Gag protein and the ability to infect and replicate in vitro. These results indicate that VpxPR(M) specifically inhibited the function of the viral protease and provide for the first time proof of principle that the incorporation of foreign proteins into virions via fusion with Vpx can inhibit HIV replication. The use of accessory proteins as vehicles to deliver deleterious proteins to virions, including dominant negative mutants of Pol proteins, may provide new opportunities for application of gene therapy-based antiretroviral strategies. The ability to package PR by expression in trans, independent of the Gag/Pol precursor, also represents a novel approach that may be exploited to study the function of the Pol proteins.